Void fraction measurement using electrical capacitance tomography and high speed photography - Sardeshpande, Madhavi V.; Harinarayan, Sagar; Ranade, Vivek V. (Chemical Engineering Research & Design, 2015)
Gas-liquid flows are encountered in variety of industrial applications including boilers, distillation towers, chemical reactors, oil pipelines, nuclear reactors etc. The measurement of two-phase flow parameters such as flow regime and void fraction is considerably important and play an important role in characterization of the hydrodynamic behavior of such gas-liquid two phase systems. The void fraction is a dimensionless quantity and is often termed as ``holdup or fraction'' in two-phase flows. According to industrial applications; it is essential to develop measurement technique for void fraction measurement which can work in hot and opaque systems. Therefore, an attempt was made here to establish electrical capacitance tomography (ECT) facility for measuring void fraction and flow regimes as well as develop suitable data processing methodologies. In the present work, focus was to measure void fraction using ECT technique and compares it with conventional and high speed photography technique. Therefore, that will give guidelines of using ECT technique for hot and opaque systems like boiling flows. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier BM. All rights reserved.
Keywords: ECT; Flow regimes; Two phase flow; Void fraction